Impacts and Limits of Irrigation Water Management on Wheat Yield and Quality. Issue 6 (7th September 2017) - Torrion, Jessica A.; Stougaard, Robert N.
Abstract : Greater understanding of the impacts of irrigation timing in hard red spring wheat ( Triticum aestivum L.) promotes better irrigation management, which optimizes the positive and minimizes the negative impacts on yield and quality. An experiment was conducted in 2014 to 2015 at Creston, MT. Eight cultivars (subplots) were randomly assigned to six water regimes (main plots). Aside from a rainfed check, irrigation treatments were: (i) replenishment of seasonal crop evapotranspiratory water loss via 32 mm per irrigation event (100ET); (ii) only 21 mm replenishment (66ET) per event to simulate season‐long deficit; and three treatments in which 100ET replacement was terminated prior to grain fill completion by scheduling final irrigation at respective stages of: (iii) med‐milk (100ET.MM), (iv) early milk (100ET.EM), (v) and anthesis (100ET.FL). The latter three treatments simulated end‐of‐season deficit irrigation. Irrigation treatment yields were similar, except for the lower 100ET.FL yield, indicating that wheat yield response to irrigation will be optimal in this environment as long as at least one irrigation event is supplied during grain fill. The cultivar yield responses to irrigation were similar. Irrigation increased biomass but had no impact on harvest index. Grain test weight (TWT) improved with irrigation. Falling number varied by cultivar and generally decreased with irrigation, but only significantly in 100ET, 66ET, and 100ET.MM. Irrigation improved yield and TWT, particularly during the hot and dry year. Irrigation can be terminated before completion of grain fill with no impact on yield and quality. Identification of adaptive cultivars with reduced irrigation or changing weather is necessary for improved productivity and grain quality.